New Testament Textual Criticism is dead! Long live New Testament Textual Criticism! - Botha, J. Eugene (HTS teologiese studies, 2007)
This article explores the notion that some of the basic assumptions upon which textual criticism is built, like the quest for an “original text”, have serious flaws and that much of what has been attempted the last 300 years is actually an exercise in futility. In this sense New Testament textual criticism can be declared dead. However, textual criticism, if viewed from a different perspective, can indeed be re-imagined to make a fresh and important contribution to New Testament scholarship.